2016
DOI: 10.1002/eqe.2833
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization, design and modelling of the RBRL seismic‐isolation system for lightweight structures

Abstract: The Rolling-Ball Rubber-Layer (RBRL) system was developed to enable seismic isolation of lightweight structures, such as special equipment or works of art, and is very versatile, a great range of equivalent natural frequencies and coefficients of damping being achievable through choice of the system parameters.The necessity to have a simple and effective design procedure has led to a new parametric experimentation at Tun Abdul Razak Research Centre (TARRC) on the rolling behaviour of the RBRL system and load-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In the study of Donà et al, the isolation device here proposed is similar to the RLRB isolators studied and designed in the present paper, but instead of cylinders, they used balls. The layers are flat, and the testing and auxiliary rubber recentering springs are utilized to recenter the structure after the earthquake motion.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Donà et al, the isolation device here proposed is similar to the RLRB isolators studied and designed in the present paper, but instead of cylinders, they used balls. The layers are flat, and the testing and auxiliary rubber recentering springs are utilized to recenter the structure after the earthquake motion.…”
Section: Introductionmentioning
confidence: 99%
“…The system comprises RBRL bearings and rubber recentering springs; these may be combined in single packages as shown in Figure 1 [1].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [1,2,3,4] have shown that the RBRL system has three key types of behaviour, differentiated according to the magnitude of the displacements relative to the ground.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations